Cerebrospinal fluid biomarkers in trials for Alzheimer and Parkinson diseases - Lleo, Alberto; Cavedo, Enrica; Parnetti, Lucilla; Vanderstichele, Hugo; Herukka, Sanna Kaisa; Andreasen, Niels; Ghidoni, Roberta; Lewczuk, Piotr; Jeromin, Andreas; Winblad, Bengt; Tsolaki, Magda; Mroczko, Barbara; et al. (Nature Reviews Neurology, 2015)
Alzheimer disease (AD) and Parkinson disease (PD) are the most common neurodegenerative disorders. For both diseases, early intervention is thought to be essential to the success of disease-modifying treatments. Cerebrospinal fluid (CSF) can reflect some of the pathophysiological changes that occur in the brain, and the number of CSF biomarkers under investigation in neurodegenerative conditions has grown rapidly in the past 20 years. In AD, CSF biomarkers are increasingly being used in clinical practice, and have been incorporated into the majority of clinical trials to demonstrate target engagement, to enrich or stratify patient groups, and to find evidence of disease modification. In PD, CSF biomarkers have not yet reached the clinic, but are being studied in patients with parkinsonism, and are being used in clinical trials either to monitor progression or to demonstrate target engagement and downstream effects of drugs. CSF biomarkers might also serve as surrogate markers of clinical benefit after a specific therapeutic intervention, although additional data are required. It is anticipated that CSF biomarkers will have an important role in trials aimed at disease modification in the near future. In this Review, we provide an overview of CSF biomarkers in AD and PD, and discuss their role in clinical trials.
EVALuna2:23719